SOURCES OF SUPPLY AND CATCHMENT AREAS OF WUDIL CATTLE MARKET, KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The study analyzed the supply sources and catchment areas of Wudil cattle market in Kano State. The objectives focused on types of cattle traded, supply source locations of cattle and catchment areas of buyers. Data were collected on types of cattle, sources of their supply and catchment areas of buyers using records of cattle observation and Focus Group Discussion with nine participants including the market leaders and other traders. Types of cattle were presented in table. Sources of supply of cattle and catchment areas for the market were depicted on maps using ARCGIS software. Based on colour of skin and castration, the major types of cattle supplied into the market are Baki (Ambala), Fari (Bunaji or White Fulani), Ja (Rahaji or Red Bororo), Galare (White-horned), Shodare (breed of white and red species), Nordi (breed of white and black species) and Bartandi (castrated). Cattle are supplied from three main sources: other countries (Niger Republic and Cameroun), other states in Nigeria (Taraba, Adamawa, Jigawa and Yobe) and within Kano State. The catchment areas are three: primary catchment area consisting of buyers within Kano State and neighbouring states, secondary catchment area including buyers largely from northeast (Gombe and Yobe States) and middle belt of Nigeria and tertiary catchment area consisting of all the states in the southern parts of the country. Recommendations given included development of market and transport infrastructure and further study on cattle transport and buyer characteristics
Keywords: Cattle, Supply, Catchment, Horn, Transport